Thermal performance of nanofluid in ducts with double forward-facing steps - Togun, H.; Ahmadi, G.; Abdulrazzaq, T.; Shkarah, A.J.; Kazi, Salim Newaz; Badarudin, Ahmad; Safaei, M.R. (Elsevier, 2015)
The turbulent heat transfer to nanofluid flow over double forward-facing steps was investigated numerically. The duct geometry and computational mesh were developed with ANSYS 14 ICEM. Two-dimensional governing equations were discretized and integrated using finite volume technique. The k-eopen turbulence model was used in the analysis. Al2O3 and CuO nanoparticles at volume fractions varying from 1% to 4% with water as the base fluid were employed for turbulent flow in a passage with a double forward-facing step. The effects of volume fraction and step height were compared with the base fluid thermal performance. The obtained results showed an increase in the Nusselt number with the increase in volume fraction of nanofluid, Reynolds number, and step height. A higher local Nusselt number value was found at the second step compared to the first step for all cases. Velocity contours were developed to visualize the recirculation regions before and after the first and second steps. The results also demonstrated enhanced heat transfer with the increase of nanoparticle concentration, and the largest thermal enhancement factor occurred for the highest nanoparticle volume fraction (4%) of Al2O3 considered in this investigation.